1977
DOI: 10.1073/pnas.74.3.961
|View full text |Cite
|
Sign up to set email alerts
|

Covalent linkage of a protein to a defined nucleotide sequence at the 5'-terminus of virion and replicative intermediate RNAs of poliovirus.

Abstract: Although the m7G5'ppp5'N(m)pNp "capping" group has been found on virtually all known mammalian mRNAs (1), poliovirus polyribosomal RNA has pUp at its 5'-end (2-4). Because poliovirion RNA will direct viral protein synthesis in a cell-free system (5), it was thought to be identical to polyribosomal poliovirus RNA. Instead, we found that less than 10% of the virion molecules contained a pUp 5'-end (2).Lee et al. (6) recently presented evidence that a protein might be linked to the 5'-terminus of poliovirion RNA.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
179
1
2

Year Published

1978
1978
1988
1988

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 305 publications
(184 citation statements)
references
References 16 publications
2
179
1
2
Order By: Relevance
“…(4,5). VPg is also found at the 5' end of intracellular plus and minus strand RNA, and on nascent plus strands; these observations suggest that VPg may act as a primer of poliovirus RNA synthesis (2,3,6).…”
mentioning
confidence: 86%
See 2 more Smart Citations
“…(4,5). VPg is also found at the 5' end of intracellular plus and minus strand RNA, and on nascent plus strands; these observations suggest that VPg may act as a primer of poliovirus RNA synthesis (2,3,6).…”
mentioning
confidence: 86%
“…(4,5). VPg is also found at the 5' end of intracellular plus and minus strand RNA, and on nascent plus strands; these observations suggest that VPg may act as a primer of poliovirus RNA synthesis (2,3,6).The intracellular forms of VPg and their possible role in viral replication have been studied previously using antibodies made to chemically synthesized segments of VPg (7-9). These antibodies detected no free VPg in infected cells but specifically immunoprecipitated three larger polypeptides with VPg determinants from infected cell lysates, of which the smallest one had a molecular weight of 12,000 (pre-VPg 3 or P3-9) (7-9).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the genome protein of phage 429 is needed for infectivity (Salas et al 1978) although those of the picornaviruses are not (Flanegan et al 1977;Nomoto et al 1977;Sangar et al I977). The position of the protease-sensitive structures on the molecules of nepovirus RNA is not certain, but the possession by tobacco ringspot virus RNA and tomato black ring virus RNA of poly-A tracts (M. A. Mayo, H. Barker and B. D. Harrison, unpublished results), presumably at the 3' end of the molecules, suggests that the attachment may be to the 5'end.…”
Section: Short Communicationsmentioning
confidence: 99%
“…These results suggested that TRSV-RNA may have a covalently-linked protein analogous to the 'genome protein' which was found at the 5' end of the RNA molecules, first of poliovirus (Lee et al I977;Flanegan et al 1977) and later of other picornaviruses (Sangar et al I977;Burroughs & Brown, 1978;Golini et al J978;Hruby & Roberts, I978) and of cowpea mosaic virus (Daubert et al 1978;Stanley et al 1978). In this paper we provide evidence which substantiates this analogy.…”
Section: Discussionmentioning
confidence: 99%